Effects of Thermal Radiation on Fully Developed MHD Nanofluid Flow in a Vertical Square Duct - Balla, Chandra Shekar; Alluguvelli, Ramesh; Naikoti, Kishan (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper addresses the effects of thermal radiation on fully developed flow in the containing nanoparticles in the presence of external magnetic field. A square vertical duct of side L is considered. At four sides of the duct Dirchlet boundary conditions are assumed. The governing nonlinear partial differential equations(PDE) are transformed into dimensionless PDE using suitable nondimensional parameters. Finite element method is employed to solve the highly nonlinear and coupled dimensionless PDE. The results are analyzed in terms of velocity contours and temperature distributions. It is observed that the fully developed nanofluid flow is significantly controlled by radiation and magnetic field.